Effect of Service Quality on the Satisfaction Level of Credit Card Customers - Kamar, Karnawi; Sahusilawane, Wildoms; Oktawiranti, Anggi; Cakranegara, Pandu Adi; Rahayu, Novi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the current era of development, the world of technology is in great demand by all people. Information technology has changed business strategy into something very vital. The banking industry sector places information technology as the main element that is integrated into banking activities, production information or in terms of providing banking services. The facility of providing accurate, timely and efficient information is in great demand and much needed in the sophistication of the current information age. The purpose of this study is to analyze effect of service quality on the satisfaction level of credit card customers. The type of research used is descriptive quantitative. The population in this study are 600 credit card users. Thus, the sample in this study are 86 credit card users. The method of analysis used a simple linear regression test. The results show that service quality has a positive and significant effect on the satisfaction level of credit cardcustomers.